Bone marrow derived dendritic cells from patients with multiple myeloma cultured with three distinct protocols do not bear Kaposi's sarcoma associated herpesvirus DNA - Bellos, Frauke Liana; Goldschmidt, Hartmut; Dörner, Maria; Ho, Anthony Dick; Moos, Marion (Annals of oncology, 1999)
Background - An association between Kaposi's sarcoma associated herpesvirus (KSHV) and the pathogenesis of multiple myeloma (MM) was postulated recently. The dendritic cells of patients with MM were proposed to be infected with the virus. - Patients and methods - Bone marrow mononuclear cells (MNC) of 23 patients, 22 with MM and one with MGUS, were cultured according to three distinct protocols for the generation of dendritic cells. One was essentially the stromal cell culture protocol described by Rettig et al. (Science 1997; 276: 1851-4), while the two other protocols comprised growth factors. Cultured cells were characterised by FACS analysis and assessed for the presence of KSHV DNA with a highly sensitive and specific nested PCR assay detecting the KS 330233 sequence of the virus genome followed by hybridisation with a KSHV specific oligonucleotide. - Results - FACS analysis of the cells with the specific markers CDla, CD86 and HLA-DR, characteristic for dendritic cells, revealed differences in the expression pattern depending on the protocol used. The proportion of CDla+ cells was very low in the stromal cell cultures (median 0.4%), while a higher percentage of CD14+ cells could be observed (median 37.8%). Growth factor containing cultures revealed a distinctly higher median percentage of CDla+ cells of 32.5%. The proportion of CD86+ cells varied between 10.4% and 78.5% and HLA-DR+ cells between 26% and 94.4%. Examination of those cells with PCR did not reveal positivity for KSHV in any of the 34 samples assessed. Amplification of seven samples revealed PCR products of approximately the size of the KS 330233, which, however, could not be confirmed as KSHV specific after hybridisation. - Conclusion - We have no evidence that bone marrow derived dendritic cells from patients with MM are infected with KSHV.
Gesehen am 10.12.2021